Long-Term Survival and Late Toxicity Associated With Pelvic Intensity Modulated Radiation Therapy (IMRT) for Cervical Cancer Involving CT-Based Positive Lymph Nodes - Lei, Chengzhi; Ma, Shaokang; Huang, Manni; An, Jusheng; Liang, Bin; Dai, Jianrong; Wu, Lingying (Frontiers in Oncology, 2019)
The purpose of this study was to evaluate the outcomes and toxicity experienced by cervical cancer patients with positive lymph nodes (LNs) who were treated with intensity-modulated radiation therapy (IMRT) and intracavitary brachytherapy (ICBT) plus concurrent chemotherapy. We retrospectively evaluated 108 cervical cancer patients with computed tomography (CT)-based positive LNs treated with IMRT and ICBT plus concurrent chemotherapy between 2009 and 2011. IMRT plans were designed to deliver 50 Gy to 95% of the planning target volume (PTV; cervical tumor, pelvis, and parametrium), with daily doses of 1.6–1.8 and 60–70 Gy to 95% of the planning gross tumor volume (PGTV)-LN (pelvic or para-aortic LNs), with daily doses of 2.0–2.2 Gy. Overall survival (OS) and progression-free survival (PFS) Kaplan–Meier curves were plotted. Acute and late toxicities were evaluated according to the Radiation Therapy Oncology Group and European Organization for Research and Treatment of Cancer toxicity criteria. Of the 108 cases, 45 were stage IIB and 63 were stage IIIB. The median follow-up was 65 months (range 2–83). Overall, the 5 year cumulative incidences of pelvic failure alone, distant failure alone, and synchronous pelvic and distant failure were 8.3, 12.9, and 8.3%, respectively. The 5 year OS rate was 67.6%, and the 5 year PFS rate was 53.7%. The 5 year cumulative incidence was 9.2% for late gastrointestinal and genitourinary toxicities of Grade ≥3 and 51.8% for acute leukopenia of Grade ≥3. The clinical results suggest that IMRT and ICBT with concurrent chemotherapy is an effective treatment, with acceptable toxicity, for advanced cervical cancer involving positive LNs.